Antiplatelet therapy in pregnancy: A systematic review. (June 2021) - Nana, Melanie; Morgan, Holly; Moore, Sacha; Lee, Zong Xuan; Ang, Eshen; Nelson-Piercy, Catherine
Abstract: Objective: To systematically review contemporary data on the safety of clopidogrel and newer antiplatelet agents in pregnant women, with particular attention to maternal and neonatal complications. Methods: The review protocol was published via PROSPERO (ID 42020165235) and conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Databases were searched using MeSH and free text terms encompassing the included antiplatelets, relevant indications, and pregnancy. Included studies reported the drug dose, the stage of pregnancy at which it was administered, and at least one primary or secondary outcome relating to pregnancy. The primary outcome was reporting of complications associated with antiplatelet use in pregnancy. Results: The search yielded 5271 results. 39 publications were included, incorporating 42 live births. The mean age of women was 34.6 years. Seven different antiplatelet agents were described, clopidogrel being most frequent (n = 37). 14 women received antiplatelet therapy in the first trimester. 14 women had regional anaesthesia (12 while taking clopidogrel), all without complication. Two women developed bleeding post caesarean section. There were no recorded neonatal delivery complications. Two neonates had congenital anomalies not felt to be related to maternal antiplatelet use. Conclusions: This systematic review describes outcomes for both mothers and neonates when exposed to clopidogrel at varying durations throughout gestation, and does not suggest higher than acceptable risk, with a congenital anomaly rate comparable to background risk. Evidence for other antiplatelet agents remains limited. Regional anaesthesia should be offered, with recommendation to stop prior to delivery in line with national guidance and in the context of individualised decision making. Graphical Abstract: ga1 Highlights: The study adds reassuring data on the outcomes for both mother and neonates when exposed to clopidogrel during pregnancy. Women undergoing pregnancy have increasing prevalence of hypertension and other risk factors for cardiovascular disease. Antiplatelets represent the mainstay of treatment, for which evidence in pregnancy is primarily based on expert opinion. Work which adds to the safety data for these agents is important in managing these women. We add reassuring data on clopidogrel in pregnancy, including for those recieving regional anaesthesia.